Respuesta :
Answer:
-1
Step-by-step explanation:
each successive number is subtracted 3 units
2 - 3 = -1
Hope this helps
Answer : -1
Step by step explanation
Given sequence = 11,8,5,2...., (t1,t2,t3,t4,......)
first term(a) = 1
Common difference(d) = t2-t1 = 8-11 = -3
nth term of arhmetic sequence is given by,
tn = a+(n-1)d
To calculate the 5th term(t5) of sequence substitute n = 5,a = 11,d = -3 in above formula,
t5 = 11+ (5-1)×(-3)
t5 = 11+ 4×(-3)
t5 = 11+(-12)
t5 = 11-12
t5 = -1
The next term of sequence is -1
Thanks for joining brainly community.